An Analysis of Language Style in the Song "Youth" - Dewi, Hernalia Citra; Anggraeni, Dwinesa (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2024)
The purpose of this study is to analyze and describe the language style contained in the lyrics of the song "youth" sung by Troye Sivan in the Blue Neighbourhood Album. With this research, the author hopes that readers will increase their knowledge about the study of stylistics. In addition, this research is expected to be useful to add to the study of discourse in the field of literature, especially about language styles and types of language styles. The method used in this research is descriptive analysis, and the research technique used is literature study. After conducting research, the author can conclude that there are 5 types of language styles from a total of 12 types of language styles proposed by Arp and Johnson in his book Sound and Sense: An Introduction to Poetry (2002). The following are the details of the data that have been found in this study, namely: (a) hyperbole as much as 2 data (16.7%), (b) personification as much as 1 data (8.3%), (c) synechdoche as much as 2 data (16.7%), (d) paradox as much as 3 data (25%), (e) symbol as much as 1 data (8.3%). The most dominating use of language style is paradoxical language style as much as 3 data with a percentage of 25%, and the least is hyperbole and symbol language style as much as 1 data each with a percentage of 8.3%. Paradoxical language style is the most dominant language style found in the lyrics of the song "Youth". The use of this language style aims to give a deep meaning and give a poetic effect to the lyrics sung by Troye Sivan.